Implementación del área de compras y su influencia en la calidad del servicio de la Empresa Negocios Gastronómicos JP SAC, distrito de Trujillo, año 2018 - Díaz Floriano, Segundo Manuel (2019)
This thesis aims to determine how the implementation of the purchasing area will influence the quality of service of the company Gastronomic Business JP SAC, Trujillo District, year 2018. To achieve this object a theoretical and practical analysis was carried out within the company getting to find that there was no shopping area, rather that purchases were made by the owner empirically, not having a shopping process, the different customers who visit the restaurant and the owner were taken as a population, and as It shows 86 clients that were obtained after applying simple and proprietary random sampling. It is worth mentioning that the method used is the inductive-descriptive, the information obtained is the result of applying the interview to the business owner and the customer survey, in addition to documentary analysis and direct observation. Among the specific objectives, mention is made of analyzing the current quality of service, analyzing the purchasing program and evaluating the expenses for purchases made by the company, proposing and implementing the area and finally making the comparison as it influenced the implementation of the purchasing area in the service provided Finally, it has been determined that the implementation of the purchasing area influences the quality of service of the company, because said implementation creates processes, activities, functions, information and results that are related to the quality of service.